Modeling and automation processes of water purification from multicomponent pollution - Safonyk, Andrii; Safonyk, Olga; Zhabchyk, Victoria (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
Mathematical models of the processes of cleaning liquids from multicomponent contamination by filtration, as well as diffusion-mass transfer perturbations and the development of numerical-asymptotic methods for solving the corresponding nonlinear regularly and singularly perturbed boundary value problems are shown. The construction of automation systems of corresponding treatment systems and complexes on the basis of solving model problems is presented.